2018
DOI: 10.1111/cyt.12642
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the Milan System as a risk stratification tool for salivary gland fine needle aspiration cytology specimens

Abstract: Objective: To perform a retrospective investigation of our institutional experience with salivary gland fine needle aspirations (FNA) through the framework of The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) and assess the risks of neoplasm and malignancy for each diagnostic category.were retrospectively categorised according to the MSRSGC. When available, preoperative cytological results were correlated with subsequent histological follow-up. Results: In total, 893 FNAs were reviewed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
129
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(176 citation statements)
references
References 27 publications
37
129
10
Order By: Relevance
“…Our ROM findings are largely comparable to other such studies recently published in the literature, which report similar findings (Table including that of a large meta‐analysis of 92 studies. The calculated ROMs in our cohort appear to be on a par with those found in similar salivary gland studies in the current literature.…”
Section: Discussionsupporting
confidence: 92%
“…Our ROM findings are largely comparable to other such studies recently published in the literature, which report similar findings (Table including that of a large meta‐analysis of 92 studies. The calculated ROMs in our cohort appear to be on a par with those found in similar salivary gland studies in the current literature.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, PA and Warthin's tumours were the most frequent diagnoses (respectively 27.1% and 16.8% of total cases). This is consistent with the frequency reported in the literature [9,10,14,15]. These diagnoses are indeed straightforward for representative samples.…”
Section: Discussionsupporting
confidence: 91%
“…The three other cases which were suspicious for epithelial malignancy were finally diagnosed as non-neoplastic (myofibroblastic granuloma) or benign neoplasm (two PA). Though, the ROM for SM is consistent with the MSRSGC (68.8% vs. 60%) and with the literature (68,8% vs. 79%, 59%, 58%) [9,11,16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results of several studies that analysed distribution of cases and estimated ROM in each MSRSGC category show that FNA cytology is an effective diagnostic procedure and confirmed the validity and diagnostic utility of MSRSGC, further revealing that ROMs of each category were broadly in line with those suggested in MSRSGC. In some of these studies, higher ROM for AUS category than in MSRSGC was observed, which probably resulted from the lower number or heterogeneity of AUS patients in these studies …”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 92%